Leveraging a Podcast Series for Nutrition Education in Medical Curriculum - John Vellek; Jessica Rosen; Gillian Hecht; Francesco Ciuffo; Rachel Thommen; Kristina H. Petersen (University Library System, University of Pittsburgh, 2024)
Background: Malnutrition is a worldwide problem. Despite the paradoxical global prevalence of both an obese and underfed population, physicians have historically fallen short in their efforts to combat this epidemic. Unfortunately, medical education has only recently prioritized nutrition curriculum, and its incorporation has been slow. The Culinary Medicine Interest Group (CMIG) at New York Medical College (NYMC) aims to expand access to nutrition education in medical school. Methods: The CMIG podcast was conceived as an adjunct to the preclinical curriculum. Podcasts were distributed via the NYMC learning-management system in parallel with pre-clinical curriculum and made widely available via Spotify, YouTube, and Google Podcasts. A pre-podcast survey was conducted to establish a baseline of nutrition knowledge in the NYMC student population, and a post-podcast survey was also distributed. Results: During 2022-2023, twelve episodes covering various nutrition-related subspecialty topics were released. We received 76 pre-podcast survey responses which made the need for nutrition curriculum clear: 37% reported no experience with nutrition, less than half took coursework that covered nutrition, 59% were uncomfortable discussing eating disorders, and only 21.5% reported feeling comfortable discussing diet in relation to menopause.  Post-podcast survey responses could not be analyzed due to low participation. Conclusion: Limited survey responses hinder conclusions about the podcast's potential impact; we believe this is related to the lack of value conferred upon content beyond the scope of mandated material. Nevertheless, baseline data support the need for more nutrition curriculum; we present a novel approach to expanding access to nutrition curriculum in medical education.